Celiac Disease and Its Association with Organ-Specific Auto-Immune Diseases - Buchke, Sakshi; Bora, Anusuiya; Mehta, Bhavika; Relekar, Maitrali; Varsha, Piyush; Kumar, Jitendra; Bhanu, Piyush (International Journal of Innovative Research in Medical Science, 2021)
Wheat is one of the most consumed foods in the world. Although it is extremely nutrient rich for us humans, some of us have great difficulties in completely digesting its protein subunits. This review aims to understand the onset of Celiac Disease and its association with several other auto-immune diseases. The gliadin molecule, undigested in the small intestine, over time, ruptures the villi lining of the intestinal wall and enters the bloodstream which in turn activates the body's immune response. In some patients with the presence of HLA DQ2/DQ8 genes, this immune response results in Celiac Disease. Notably, researchers over the past several decades have found several links between Celiac Disease and multiple auto-immune diseases. Diabetes is one such auto-immune disease which has shown multiple associations with Celiac Disease. Similarly, in this review paper, we are critically analyzing the association of Celiac Disease with some of the most common autoimmune diseases namely Type-1 Diabetes, Multiple Sclerosis, Autism and Inflammatory Bowel Disease. In this paper, we have shown a clear correlation of celiac disease with several other auto-immune diseases. Further study is needed to understand the bidirectional association of Celiac Disease with different auto-immune diseases.